Cita & Impian Masyarakat Karacak Leuwiliang Bogor - Lusi Mariana; Evinovita Evinovita (El-Mujtama: Jurnal Pengabdian Masyarakat, 2021)
This community service activity aims to provide opportunities for students to apply knowledge to build public awareness in preventing and overcoming the problem of the Covid-19 pandemic. The activity took place in Karacak Village, Leuwiliang District, Bogor, West Java. The method used is descriptive qualitative analysis based on observation and community participation in the field. The domicile-based thematic KKN was filled with activities for attaching posters, distributing masks, learning assistance, reading aids, work assistance, making hand sanitizers, socializing good hand washing, happy healthy exercise, and teaching assistance at TPQ Barkatul Huda in Kp. Lebak Sirna Rt 04/03 Karacak Village. The positive response given by residents is very diverse. The average citizen gave a good response to the holding of this domicile-based KKN.